The Role of MicroRNAs in the Regulation of K+ Channels in Epithelial Tissue - Pilmore, Elliot; Hamilton, Kirk L. (Frontiers in Physiology, 2015)
Our understanding of the modulation of proteins has shifted in direction with the discovery of microRNAs (miRs) over twenty years ago. MiRs are now in the ‘limelight’ as these non-coding pieces of RNA (generally 22 nucleotides long) result in altered translation and function of proteins. Indeed, miRs are now reported to be potential biomarkers of disease. Epithelial K channels play many roles in electrolyte and fluid homeostasis of the human body and have been suggested to be therapeutic targets of disease. Interestingly, the role of miRs in modulating K channels of epithelial tissues is only emerging now. This minireview focuses on recent novel findings into the role of miRs in the regulation of K channels of epithelia.